Executive attention and its relationship to psychological empowerment among faculty members in the Faculties of Physical Education and Sports Sciences - انور عبدالقادر ماشي (الرياضة المعاصرة)
The research aims to know the executive attention and its relationship to psychological empowerment in the Faculties of Physical Education and Sports Sciences among the faculty members and in the variables of the study, the two researchers used the descriptive approach to suit it to the nature of the research. As for the research sample, it was represented by a group of male and female physical education teachers in four universities of (100) teaching staff And teaching